Investigating the Effects of Mobada Game-Based Learning on Student Activeness in Elementary Mathematics: A Constructivist Perspective - Devyana Puspasari Purnomo; Tia Latifatu Sadiah; Ayu Fitri (Jurnal Didactical Mathematics, 2026)
This study investigates the effect of Mobada (Monopoly of Plane Figures) as a game-based learning medium on students’ learning activeness in elementary mathematics classrooms. A quantitative pre-experimental approach with a one-group pretest–posttest design was employed, involving 38 fifth-grade students. Data were collected using a validated questionnaire that measured multiple dimensions of learning activity, including participation, attention, and collaboration. Statistical analysis using a paired-samples t-test revealed a significant improvement in students’ activity after the intervention (p < 0.05). The findings were further strengthened by an extremely large effect size (d = 2.74), indicating substantial practical impact. These results suggest that integrating game-based learning creates an interactive, student-centered environment that effectively promotes behavioral engagement. However, the absence of a control group limits causal inference. This study contributes to the literature by positioning learning activeness as a primary outcome and highlighting the role of game-based instructional media in enhancing engagement in mathematics education